Cisplatin overcomes radiotherapy resistance in OCT4-expressing head and neck squamous cell carcinoma - Routila Johannes; Qiao Xi; Weltner Jere; Rantala Juha K; Carpén Timo; Hagström Jaana; Mäkitie Antti; Leivo Ilmo; Ruuskanen Miia; Söderlund Jenni; Rintala Marjut; Hietanen Sakari; et al. (Elsevier, 2022)
Objectives: Cisplatin is combined with radiotherapy for advanced head and neck squamous cell carcinoma (HNSCC). While providing a beneficial effect on survival, it also causes side effects and thus is an important target when considering treatment de-escalation. Currently, there are no biomarkers to predict its patient-selective therapeutic utility. In this study, we examined the role of the stem cell factor OCT4 as a potential biomarker to help clinicians stratify HNSCC patients between radiotherapy and chemoradiotherapy.
Materials and methods: OCT4 immunohistochemical staining of a population-validated tissue microarray (PV-TMA) (n = 166) representative of a standard HNSCC patients was carried out, and 5-year survival was analyzed. The results were validated using ex vivo drug sensitivity analysis of HNSCC tumor samples, and further cross-validated in independent oropharyngeal (n = 118), nasopharyngeal (n = 170), and vulvar carcinoma (n = 95) clinical datasets. In vitro, genetically modified, patient-derived HNSCC cells were used.
Results: OCT4 expression in HNSCC tumors was associated with radioresistance. However, combination therapy with cisplatin was found to overcome thisradioresistance in OCT4-expressing HNSCC tumors. The results were validated by using several independent patient cohorts. Furthermore, CRISPRa-based OCT4 overexpression in the HNSCC cell line resulted in apoptosis resistance, and cisplatin was found to downregulate OCT4 protein expression in vitro. Ex vivo drug sensitivity analysis of HNSCC tumors confirmed the association between OCT4 expression and cisplatin sensitivity.
Conclusion: This study introduces OCT4 immunohistochemistry as a simple and cost-effective diagnostic approach for clinical practice to identify HNSCC patients benefitting from radiosensitization by cisplatin using either full or reduced dosing.